Ulcerative Colitis and Nursing - İlknur Yücel (KHD Production, 2023)
Ulcerative colitis is a chronic disease of attacks and remissions characterized by bloody diarrhea, abdominal pain, and abdominal cramps involving the colonic mucosa starting from the rectum. The etiology and pathogenesis of ulcerative colitis are unknown. The most common signs and symptoms of ulcerative colitis are bloody diarrhea, abdominal pain, and abdominal cramps. Nurses, who are health professionals, are obligated to take the symptoms and signs under control and to care for patients through the treatment planned by the physician. Patient care is very important in the nursing profession. The nurse's primary role is to support the patient and his/her family to live a long, trouble-free life and comply with the treatment. This study aims to give information about Ulcerative Colitis and to discuss the nursing approach to providing professional health care.